Modelling of Solitary Wave Run-up on an Onshore Coastal Cliff by Smoothed Particle Hydrodynamics Method - Jian, Wei (2015)
The solitary wave run-up in the presence of an onshore coastal cliff is investigated using the Smoothed Particle Hydrodynamics (SPH) method. A composite topography made of a steep slope, a gentle beach and a steep coastal cliff was used in the experimental and numerical studies to represent real life scenarios. Comparison with laboratory measurements shows that the SPH model is able to capture the evolution and run-up of solitary waves for both non-breaking and slight breaking cases with reasonable accuracy.